Prevalence and Factors Associated with Respiratory Symptoms Among Bahir Dar Textile Industry Workers, Amhara Region, Ethiopia - Kifle, Manay (Environ Health Insights, 2020)
INTRODUCTION: The expansions of labor-intensive investments in a developing countries, especially in textile production create a dusty work environment for workers, and those workers are from the low socio-economic group and need special safety concern. OBJECTIVE: This study was aimed at assessing the prevalence of respiratory symptoms and associated factors among textile factories workers in Bahir Dar, Amhara region, Ethiopia, 2015. METHODS: Institutional based cross-sectional study design was employed among randomly selected 384 textile workers using pre-tested interviewer-administered questionnaire. We stratified workers by their working section in the textile industries. Then the proportional numbers of workers were selected from each working section of the factory by using a random number generator. The identification number of workers from each factory was used for selection. The data were checked, coded, and entered to Epi-info Version 7 and exported to the Statistical Package for Social Science Version 20 for further analysis. Both bivariate and multivariate logistic regressions were used to identify associated factors. Variables having a P ⩽ .2 were fitted to multivariate logistic regression so as to assess the presence and strength of association with the respiratory symptom. Variables having a P < .05 were considered as significant. RESULTS: Three hundred eighty-three (99.74%) of the study participants responded completely filling the questionnaire. In this study, the prevalence of cough, phlegm, bronchitis, chronic bronchitis, and chest pain among the respondents were 31 (8.1%), 45 (11.7%), 26 (6.8%), 2 (0.5%), and 21 (5.5%), respectively. Generally, 141 (36.81%) of the respondents have either of the above respiratory symptoms in the textile industry. Working in the spinning section (AOR = 3.26, 95% CI: 1.80, 5.89), being in the grade 11 and 12 level and below (AOR = 2.36, 95% CI: 1.50, 3.70) and personal protective equipment (PPE) utilization (AOR = 4.88 95% CI: 1.54-15.45) were significantly associated with respiratory symptoms in the multivariate analysis. CONCLUSION: The prevalence of respiratory symptoms in Bahir Dar Textile workers was relatively high. Working department, educational status, and PPE use were variables significantly associated with respiratory symptoms in this study. Experience sharing across departments, employing educated workers and provision of personal protective equipment are important tasks to be followed to reduce respiratory symptoms in the industry.